CO46 | Comparison of reticulated platelet procoagulant role in liver cirrhosis vs. fibrosis (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Reticulated platelets (RePLTs) are bigger and more reactive than mature platelets (PLTs), with an increased content of ribonucleic acid (RNA) and directly released by megakaryocytes. In liver cirrhosis the increased platelet turnover implies the release of these “emergency platelets’’ which would contrast bleeding events that can occur due to reduced synthesis of hepatic-dependent coagulation factors and to contrast peripheral platelet destruction. Although the role of RePLTs in the hemostatic balance in cirrhotic patients is not well defined, even less is known about their role in patients with Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD). The aim of this study is to compare the percentage and activation of RePLTs vs. PLTs in patients with cirrhosis and MASLD.